Stringer-Panel Models in Structural Concrete Applied to D-region Design - Blaauwendraad, Johan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Structural concrete designers nowadays distinguish between B-regions (named after Bernoulli beam theory) and D-regions (D standing for 'disturbed'). They are all familiar with B-regions, but less acquainted with the expertise required for D-regions. To design D-regions, the Strut-and-Tie Model (STM) is usually applied, a model laid down worldwide in structural codes of practice. The Stringer-Panel Model (SPM) recommended here is a companion method to the STM, with the advantage of being suitable for different load cases and reversed loading. This being so, the SPM is suitable for linear-elastic analyses where durability is a key consideration, but also suits structural design for contexts of cyclical seismic activity. Finally, this book sets out how structural engineers who prefer the STM can nevertheless apply the SPM to determine a proper strut-and-tie model.
1. Introduction -- 2. Dapped beam.-3. Beam with recess -- 4. Frame joints and corbels -- 5. Opening in box web -- 6. Console with opening -- 7. Deep beam with opening -- 8. Wall with large opening -- 9. Integral Bridge -- 10. Diaphragm floor slab -- Appendix 1 Linear-elastic analysis using the program SPM.py -- Appendix 2 Linear-elastic analysis using Matlab code and SAP2000.
Keywords: Mechanics, Applied; Solids; Building materials; Solid Mechanics; Structural Materials; Building Materials